Mutations in GRK2 cause Jeune syndrome by impairing Hedgehog and canonical Wnt signaling. - Bosakova, Michaela; AbrAHm, Sara P; Nita, Alexandru; Hruba, Eva; Buchtova, Marcela; Taylor, S Paige; Duran, Ivan; Martin, Jorge; Svozilova, Katerina; Barta, Tomas; Varecha, Miroslav; Balek, Lukas; et al. (EMBO Mol Med, 2020)
Mutations in genes affecting primary cilia cause ciliopathies, a diverse group of disorders often affecting skeletal development. This includes Jeune syndrome or asphyxiating thoracic dystrophy (ATD), an autosomal recessive skeletal disorder. Unraveling the responsible molecular pathology helps illuminate mechanisms responsible for functional primary cilia. We identified two families with ATD caused by loss-of-function mutations in the gene encoding adrenergic receptor kinase 1 (ADRBK1 or GRK2). GRK2 cells from an affected individual homozygous for the p.R158* mutation resulted in loss of GRK2, and disrupted chondrocyte growth and differentiation in the cartilage growth plate. GRK2 null cells displayed normal cilia morphology, yet loss of GRK2 compromised cilia-based signaling of Hedgehog (Hh) pathway. Canonical Wnt signaling was also impaired, manifested as a failure to respond to Wnt ligand due to impaired phosphorylation of the Wnt co-receptor LRP6. We have identified GRK2 as an essential regulator of skeletogenesis and demonstrate how both Hh and Wnt signaling mechanistically contribute to skeletal ciliopathies.

Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies. - Zhang, Wenjuan; Taylor, S Paige; Ennis, Hayley A; Forlenza, Kimberly N; Duran, Ivan; Li, Bing; Sanchez, Jorge A Ortiz; Nevarez, Lisette; Nickerson, Deborah A; Bamshad, Michael; Lachman, Ralph S; Krakow, Deborah; et al. (Hum Mutat, 2018)
Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasia (CED) phenotypes. To identify new genes and define the spectrum of mutations in the skeletal ciliopathies, we analyzed 152 unrelated families with SRPS, ATD, and EVC. Causal variants were discovered in 14 genes in 120 families, including one newly associated gene and two genes previously associated with other ciliopathies. These three genes encode components of three different ciliary complexes; FUZ, which encodes a planar cell polarity complex molecule; TRAF3IP1, which encodes an anterograde ciliary transport protein; and LBR, which encodes a nuclear membrane protein with sterol reductase activity. The results established the molecular basis of SRPS type IV, in which mutations were identified in four different ciliary genes. The data provide systematic insight regarding the genotypes associated with a large cohort of these genetically heterogeneous phenotypes and identified new ciliary components required for normal skeletal development.
Keywords: Ciliopathies; Cytoplasmic Dyneins; Genetic Association Studies; Genetic Markers; Genetic Variation; Genotype; Humans; Mutation; Phenotype; Proteins; Radiography; Skeleton; Whole Exome Sequencing

Mutations in IFT-A satellite core component genes and produce short rib polydactyly syndrome with distinctive campomelia. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Qureshi, Faisal; Jacques, Suzanne M; Wallerstein, Robert; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Cilia, 2017)
BACKGROUND: Skeletal ciliopathies comprise a spectrum of ciliary malfunction disorders that have a profound effect on the skeleton. Most common among these disorders is short rib polydactyly syndrome (SRPS), a recessively inherited perinatal lethal condition characterized by a long narrow chest, markedly shortened long bones, polydactyly and, often, multi-organ system involvement. SRPS shows extensive locus heterogeneity with mutations in genes encoding proteins that participate in cilia formation and/or function. RESULTS: Herein we describe mutations in , a satellite member of the retrograde IFT-A complex, that produce a form of SRPS with unusual bending of the ribs and appendicular bones. These newly described mutations disrupted cilia formation, produced abnormalities in cartilage growth plate architecture thus contributing to altered endochondral ossification. We further show that the SRPS phenotype is similar to SRPS resulting from mutations in the gene encoding IFT121 (WDR35), a direct interactor with IFT43. CONCLUSIONS: This study defines a new -associated phenotype, identifying an additional locus for SRPS. The data demonstrate that IFT43 is essential for ciliogenesis and that the mutations disrupted the orderly proliferation and differentiation of growth plate chondrocytes, resulting in a severe effect on endochondral ossification and mineralization. Phenotypic similarities with SRPS cases resulting from mutations in the gene encoding the IFT43 direct interacting protein IFT121 suggests that similar mechanisms may be disrupted by defects in these two IFT-A satellite interactors.

The ciliopathy-associated CPLANE proteins direct basal body recruitment of intraflagellar transport machinery. - Toriyama, Michinori; Lee, Chanjae; Taylor, S Paige; Duran, Ivan; Cohn, Daniel H; Bruel, Ange-Line; Tabler, Jacqueline M; Drew, Kevin; Kelly, Marcus R; Kim, Sukyoung; Park, Tae Joo; Braun, Daniela A; et al. (Nat Genet, 2016)
Cilia use microtubule-based intraflagellar transport (IFT) to organize intercellular signaling. Ciliopathies are a spectrum of human diseases resulting from defects in cilia structure or function. The mechanisms regulating the assembly of ciliary multiprotein complexes and the transport of these complexes to the base of cilia remain largely unknown. Combining proteomics, in vivo imaging and genetic analysis of proteins linked to planar cell polarity (Inturned, Fuzzy and Wdpcp), we identified and characterized a new genetic module, which we term CPLANE (ciliogenesis and planar polarity effector), and an extensive associated protein network. CPLANE proteins physically and functionally interact with the poorly understood ciliopathy-associated protein Jbts17 at basal bodies, where they act to recruit a specific subset of IFT-A proteins. In the absence of CPLANE, defective IFT-A particles enter the axoneme and IFT-B trafficking is severely perturbed. Accordingly, mutation of CPLANE genes elicits specific ciliopathy phenotypes in mouse models and is associated with ciliopathies in human patients.
Keywords: Animals; Ciliopathies; Flagella; Humans; Mice; Mutation; Phenotype; Protein Binding; Protein Transport; Proteins

Destabilization of the IFT-B cilia core complex due to mutations in IFT81 causes a Spectrum of Short-Rib Polydactyly Syndrome. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Forlenza, Kimberly N; Spiro, Rhonda P; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Sci Rep, 2016)
Short-rib polydactyly syndromes (SRPS) and Asphyxiating thoracic dystrophy (ATD) or Jeune Syndrome are recessively inherited skeletal ciliopathies characterized by profound skeletal abnormalities and are frequently associated with polydactyly and multiorgan system involvement. SRPS are produced by mutations in genes that participate in the formation and function of primary cilia and usually result from disruption of retrograde intraflagellar (IFT) transport of the cilium. Herein we describe a new spectrum of SRPS caused by mutations in the gene IFT81, a key component of the IFT-B complex essential for anterograde transport. In mutant chondrocytes, the mutations led to low levels of IFT81 and mutant cells produced elongated cilia, had altered hedgehog signaling, had increased post-translation modification of tubulin, and showed evidence of destabilization of additional anterograde transport complex components. These findings demonstrate the importance of IFT81 in the skeleton, its role in the anterograde transport complex, and expand the number of loci associated with SRPS.

IFT52 mutations destabilize anterograde complex assembly, disrupt ciliogenesis and result in short rib polydactyly syndrome. - Zhang, Wenjuan; Taylor, S Paige; Nevarez, Lisette; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Krakow, Deborah; Cohn, Daniel H (Hum Mol Genet, 2016)
The short-rib polydactyly syndromes (SRPS) encompass a radiographically and genetically heterogeneous group of skeletal ciliopathies that are characterized by a long narrow chest, short extremities, and variable occurrence of polydactyly. Radiographic abnormalities include undermineralization of the calvarium, shortened and bowed appendicular bones, trident shaped acetabula and polydactyly. In a case of SRPS we identified compound heterozygosity for mutations in IFT52, which encodes a component of the anterograde intraflagellar transport complex. The IFT52 mutant cells synthesized a significantly reduced amount of IFT52 protein, leading to reduced synthesis of IFT74, IFT81, IFT88 and ARL13B, other key anterograde complex members. Ciliogenesis was also disrupted in the mutant cells, with a 60% reduction in the presence of cilia on mutant cells and loss of cilia length regulation for the cells with cilia. These data demonstrate that IFT52 is essential for anterograde complex integrity and for the biosynthesis and maintenance of cilia. The data identify a new locus for SRPS and show that IFT52 mutations result in a ciliopathy with primary effects on the skeleton.
Keywords: Carrier Proteins; Cilia; Ciliopathies; Cytoskeletal Proteins; Flagella; Humans; Intracellular Signaling Peptides and Proteins; Multiprotein Complexes; Muscle Proteins; Mutation; Short Rib-Polydactyly Syndrome; Skeleton; Tumor Suppressor Proteins

Mutations in DYNC2LI1 disrupt cilia function and cause short rib polydactyly syndrome. - Taylor, S Paige; Dantas, Tiago J; Duran, Ivan; Wu, Sulin; Lachman, Ralph S; Nelson, Stanley F; Cohn, Daniel H; Vallee, Richard B; Krakow, Deborah (Nat Commun, 2015)
The short rib polydactyly syndromes (SRPSs) are a heterogeneous group of autosomal recessive, perinatal lethal skeletal disorders characterized primarily by short, horizontal ribs, short limbs and polydactyly. Mutations in several genes affecting intraflagellar transport (IFT) cause SRPS but they do not account for all cases. Here we identify an additional SRPS gene and further unravel the functional basis for IFT. We perform whole-exome sequencing and identify mutations in a new disease-producing gene, cytoplasmic dynein-2 light intermediate chain 1, DYNC2LI1, segregating with disease in three families. Using primary fibroblasts, we show that DYNC2LI1 is essential for dynein-2 complex stability and that mutations in DYNC2LI1 result in variable length, including hyperelongated, cilia, Hedgehog pathway impairment and ciliary IFT accumulations. The findings in this study expand our understanding of SRPS locus heterogeneity and demonstrate the importance of DYNC2LI1 in dynein-2 complex stability, cilium function, Hedgehog regulation and skeletogenesis.
Keywords: Biological Transport; Cilia; Cytoplasmic Dyneins; Cytoskeleton; Female; Fibroblasts; Flagella; Hedgehog Proteins; Humans; Male; Mutation; Pedigree; Short Rib-Polydactyly Syndrome